Exploring Role model, Parenting and Juvenile Delinquents in the Selected Poems - Ayesha Mohammed Ibrahim (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
“What Children see, Children do”, role modeling is a momentous progression in child’s life. All children have role model at some point in their lives. The point is who they see as their model. This may seem trivial whereas it creates an enormous impression on the impending behaviour and resolutions of the child. It is important for a child to have a social life. Peer and community may also affect the antisocial behaviour of a child. If a child is antisocial or excluded by the peer group, this may lead to stress, apprehension and downheartedness and may even shoddier psychological disturbances. This escalates the risk of crime among juveniles. There are various reasons for delinquency it can be psychological, economic, political and social. This paper tries to answer the questions, whether Juvenile Delinquency is a social issue and how it can be recognized in the teaching or learning environment and what are the implications of Juvenile Delinquency for teachers and students. It also analyses role modeling and parenting in the selected poems in the anthology titled Teen Poems from behind Bars poems written by youth at Denney Justice Center in Everett, Washington.